Effect of Intraoperative Corneal Stromal Pocket Irrigation in Small Incision Lenticule Extraction - Liu, Yu-Chi (2015)
This study aimed at evaluating the effect of intraoperative corneal pocket irrigation in small incision lenticule extraction (SMILE) and compares it to that in femtosecond laser-assisted in situ keratomileusis (FS-LASIK). Sixteen rabbit eyes underwent a SMILE procedure, with 8 eyes having corneal pocket irrigation, while the other 8 eyes were without irrigation. Another 16 eyes underwent a FS-LASIK procedure for comparison, with 8 eyes having flap irrigation, while the other 8 eyes were without irrigation. The results showed that the changes in the total corneal thickness, anterior and posterior lamellar thickness, measured by the anterior segment optical coherence tomography, were comparable between the SMILE with and without irrigation groups, suggesting that the irrigation did not lead to significant changes in the corneal thickness. However, at postoperative 8 hours, in vivo confocal microscopy showed that the interface reflectivity in the SMILE with irrigation group was significantly higher than that in other three groups. The presence of interface fluid was further confirmed by the identification of fluid pockets with undulated collagen shown on histological section in the post-SMILE with irrigation eyes. Our findings might contribute to the occurrence of post-SMILE delayed immediate visual quality recovery and further clinical study is required.